2018
DOI: 10.1016/j.bjm.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of procedures for binding of aflatoxin M1 to Lactobacillus rhamnosus GG

Abstract: Several strains of lactic acid bacteria (LAB), frequently used in food fermentation and preservation, have been reported to bind different types of toxins in liquid media. This study was carried out to investigate the effect of different concentrations of Lactobacillus rhamnosus GG (ATCC 53103) to bind aflatoxin M1 (AFM1) in liquid media. AFM1 binding was tested following repetitive washes or filtration procedures in combination with additional treatments such as heating, pipetting, and centrifugation. The mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 24 publications
4
48
0
1
Order By: Relevance
“…This is in line with the fact that the best ability of LAB to convert milk to traditional fermented milk is achieved at higher temperatures of 25–30 °C (Adamberg, Kask, Laht, & Paalme, ) and conversely, increase of temperature remarkably raised AFM1/probiotic binding from the milk when exposed to L. rhamnosus GG (Assaf et al, ). In our study, the combination of the two bacteria compensated this gap and could increase the AFM1 removal potential from Doogh as far as the percentage of AFM1 removal reached 100% at each time of the sampling while it was produced through the industrial process.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This is in line with the fact that the best ability of LAB to convert milk to traditional fermented milk is achieved at higher temperatures of 25–30 °C (Adamberg, Kask, Laht, & Paalme, ) and conversely, increase of temperature remarkably raised AFM1/probiotic binding from the milk when exposed to L. rhamnosus GG (Assaf et al, ). In our study, the combination of the two bacteria compensated this gap and could increase the AFM1 removal potential from Doogh as far as the percentage of AFM1 removal reached 100% at each time of the sampling while it was produced through the industrial process.…”
Section: Discussionsupporting
confidence: 55%
“…Until now, chemical, physical, or biological methods or compounds have been used to assess their ability in removing AF from milk and other dairy products (Assaf, Atoui, Khoury, Chokr, & Louka, ). The impression of probiotic‐based detoxification has been confirmed by outcomes from several studies, which were accomplished for milk and other dairy products as one of the dietary strategies to prevent human from being contaminated with aflatoxin (Redzwan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Assaf, Atoui, Khoury, Chokr, and Louka () have shown that both hydrogen bonds and Van der Waals interactions play crucial roles in aflatoxin and bacteria binding. Their results also showed that binding capacities could be correlated with some extent reversible interactions where AFM 1 can be removed if the solutions containing bounded AFM 1 is repeatedly washed.…”
Section: Detoxification Mechanisms Of Afm1mentioning
confidence: 99%
“…The change in the binding rate of AFM1 during the elution of the complex by washing is presented in Figure , which shows that the elution process resulted in a decrease in the AFM1 binding rate. This decrease in AFM1 binding may be due to unbound AFM1 aggregated among the bacteria or the disruption of the weak bonds established with AFM1, and the dissociative AFM1 may return back into the solution after washing (Assaf et al, ). The elution had the greatest influence on the binding rate of AFM1 in the control group (untreated bacteria), which decreased from 67.93 ± 0.34% to 48.85 ± 1.23%.…”
Section: Resultsmentioning
confidence: 99%